No link between population isolation and speciation rate in squamate reptiles - Singhal, Sonal; Colli, Guarino R; Grundler, Maggie R; Costa, Gabriel C; Prates, Ivan; Rabosky, Daniel L (Proceedings of the National Academy of Sciences - PNAS, 2022)
Rates of species formation vary widely across the tree of life and contribute to massive disparities in species richness among clades. This variation can emerge from differences in metapopulation-level processes that affect the rates at which lineages diverge, persist, and evolve reproductive barriers and ecological differentiation. For example, populations that evolve reproductive barriers quickly should form new species at faster rates than populations that acquire reproductive barriers more slowly. This expectation implicitly links microevolutionary processes (the evolution of populations) and macroevolutionary patterns (the profound disparity in speciation rate across taxa). Here, leveraging extensive field sampling from the Neotropical Cerrado biome in a biogeographically controlled natural experiment, we test the role of an important microevolutionary process-the propensity for population isolation-as a control on speciation rate in lizards and snakes. By quantifying population genomic structure across a set of codistributed taxa with extensive and phylogenetically independent variation in speciation rate, we show that broad-scale patterns of species formation are decoupled from demographic and genetic processes that promote the formation of population isolates. Population isolation is likely a critical stage of speciation for many taxa, but our results suggest that interspecific variability in the propensity for isolation has little influence on speciation rates. These results suggest that other stages of speciation-including the rate at which reproductive barriers evolve and the extent to which newly formed populations persist-are likely to play a larger role than population isolation in controlling speciation rate variation in squamates.